British Society of Interventional Radiology Iliac Angioplasty and Stent Registry: fourth report on an additional 8, 294 procedures. Issue 6 (June 2019) - Miller, C.; Frood, R.; See, T.C.; Hammond, C.J.
Abstract : AIM: To provide an update of current practice in iliac artery intervention in the UK. MATERIALS AND METHODS: Ninety-nine interventional units across the UK completed online submission forms for iliac angioplasty and stent procedures between 2011 and 2014 (inclusive) for the British Iliac Angioplasty and Stenting (BIAS) IV registry. RESULTS: Data for 8, 294 procedures were submitted during the study period. A total of 12, 253 iliac segments were treated in 10, 311 legs. The commonest indication was claudication ( n= 5219, 64.4%). Of the cases performed, 6, 582 (80.8%) were performed electively with 3, 548 (44.8%) of the procedures performed as a day-case and 6, 586 (54%) of the lesions were treated with stents. Successful endovascular intervention (residual stenosis ≤49%) was achieved in 11, 847 (97%) of treated segments, with residual stenosis in 1.5%. One point five percent of lesions could not be crossed with a wire. Limb complications were recorded in 366 (3.5%), resulting in 141 patients undergoing an unplanned intervention and 173 (2.2%) patients had a systemic complication. There were 84 deaths prior to discharge, of which 13 (15%) were procedure related. Both systemic and limb complication rates were higher in patients undergoing treatment for critical ischaemia. CONCLUSION: Iliac stenting and angioplasty are associated with high technical success with a low complication rate. These data provide up-to-date statistics for patient information and future audit and benchmarking purposes. Highlights: This report provides registry data on 8294 patients undergoing iliac angioplasty and stenting in the United Kingdom. Technical success of iliac angioplasty and stenting is high, being achieved in 97% of lesions. Complication rates are 3.5% (limb complications) and 2.2% (systemic complications). These data provide benchmarking criteria for audit and statistics for patient information.